Role of Matrix Metalloproteinase-8 in Atherosclerosis - Lenglet, Sébastien; Mach, François; Montecucco, Fabrizio (Mediators of Inflammation, 2013)
Plaque rupture is the main cause of acute myocardial infarction and stroke. Atherosclerotic plaques have been described to be vulnerable and more prone to rupture when they are characterized by thin, highly inflamed, and collagen-poor fibrous caps and contain elevated levels of proteases, including metalloproteinases (MMPs). Initiation of collagen breakdown in plaques requires interstitial collagenases, a MMP subfamily consisting of MMP-1, MMP-8, and MMP-13. Previous reports demonstrated that MMP-1 and MMP-13 might be overexpressed in both human and experimental atherosclerosis. Since neutrophils have been only recently reported in atherosclerotic plaques, the role of MMP-8 (formerly known as “neutrophil collagenase”) was only marginally evaluated. In this paper, we will update and comment on evidence of the most relevant regulatory pathways and activities mediated by MMP-8 in atherogenesis.